Il femminino in Ger 2,1-4,4 - Lopasso, Vincenzo (Liber Annuus, 2012)
Abstract Jeremiah 2:1-4:4 consists of oracles belonging to the first predication of the prophet. Although its temporal limits and identification are still debatable, they present some of the connections with the matured theology of Jeremiah, centred on the New Covenant. In these oracles, the prophet is more concerned to convince the nation the necessity of conversion. Through rhetorical means, which he uses to communicate the message and to reinforce his argumentation, the prophet outlines the image of Judah strongly characterized in a sexual sense. Lopasso here concentrates on the religious message, explaining the scope for which some of the figures and rhetorical means are used and examines the original life-setting (background) of some of the oracles.